SPURIOUS ACTIVATION ASSESSMENT OF THERMAL POWER PLANT’S SAFETY-INSTRUMENTED SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Safety-instrumented systems (also called technological protections) play the significant role in prevention and mitigating of major accidents that can occur on thermal power plant. Activations of safety-instrumented system turn the power unit into safe state by shutting it down or reducing it productivity. The power generation process operates continuously. Any unplanned outage of generation equipment leads to undersupply of energy and big commercial losses to generation company. In Russia the values of allowed spurious trip rate for safety-instrumented systems are set by regulatory agency. These values are strict to all technological protections and do not take into account the differences in amounts of losses. This paper presents more flexible approach based on the Farmer’s risk criterion. Also risk reduction factor for spurious activation is proposed.